A Novel Approach for Bisphosphonates: Ionic Liquids and Organic Salts from Zoledronic Acid. (11th October 2019) - Teixeira, Sónia; Santos, Miguel M.; Ferraz, Ricardo; Prudêncio, Cristina; Fernandes, Maria H.; Costa‐Rodrigues, João; Branco, Luís C.
Abstract: Novel ionic liquids and organic salts based on mono‐ or dianionic zoledronate and protonated superbases, choline and n ‐alkylmethylimidazolium cations, were prepared and characterized by spectroscopic and thermal analyses. Most of the prepared salts display amorphous structures and very high solubility in water and saline solutions, especially the dianionic salts. Among the zoledronate‐based ionic compounds, those containing choline [Ch] and methoxyethylmethylimidazolium [C3 OMIM] cations appear to have significant cytotoxicity against human osteosarcoma cells (MG63) and low toxicity toward healthy skin fibroblast cells. Because osteosarcoma is a bone pathology characterized by an increase in bone turnover rate, the results presented herein may be a promising starting point for the development of new ionic pharmaceutical drugs against osteosarcoma. Abstract : No bones about it ! Compounds that simultaneously inhibit bone resorption while exhibiting selective cytotoxicity toward osteosarcoma cells are an important step in the development of new drugs to treat osteosarcoma. Herein we report highly soluble zoledronate‐based ionic liquids and organic salts that display these promising attributes, thus serving as suitable starting points for future anti‐osteosarcoma drugs.